Comparison of characteristics of Asian and non-Asian tourists visiting eco-lodges in Sri Lanka - Sumanapala, H. D. P.; Kotagama, S. W.; Perera, P. K. P.; Galahitiyawe, N. W. K.; Suranga, D. A. C. S. (National Science Foundation: Colombo, 2017)
As the demand for ecotourism and nature-based tourism increases, eco-lodges are becoming a popular alternative accommodation choice. Consequently, the development of an ecolodge industry has wider implications for countries such as Sri Lanka, especially when considering the country’s high potential for ecotourism and the need to provide alternative forms of accommodation for increasing tourist arrivals. In the Sri Lankan context, the eco-lodge industry still remains relatively undeveloped and the understanding of characteristics of visitors who seek accommodation in eco-lodges is limited. In this study, the author distinguished Asian and non-Asian ecotourist market segments visiting ecolodges in Sri Lanka, to enable ecotourism operators and policy makers to better tailor their products to target groups. A survey of 362 ecolodge occupants in 16 selected ecolodges found that the Asian and non-Asian visitor segments differ in terms of travel motivations, their perceptions on various ecolodge attributes, trip characteristics and demographics. However, both age and level of education were found to be strongly related in other studies. The study found that non-Asian ecotourists stay for longer periods by comparison with Asian ecotourists. Seeking novel experiences appeared to be the main motivation of Asian ecolodge occupants, and they typically demanded physically challenging activities. Non-Asians’ motivation was friendliness of the people of the host country, followed by visiting nature and learning local customs. The management implications of distinguishing the Asian and non-Asian market segments are discussed.
Keywords: Ecotourism; Ecolodge patrons; Visitor profiles; Travel characteristics; Sri Lanka